Diclofenac removal by submerged MF membrane photocatalytic reactor and coupling with RO membrane - T.V. Tung; J. Ananpattarachai; P. Kajitvichyanukul (Lowland Technology International, 2018)
The purpose of coating TiO2 on microfiltration membrane in photocatalytic membrane reactor (PMR) enhances the permeate flux and effluent quality. In this study, Nitrogen doped TiO2 (NTiO2) on ceramic membrane surface submerged in the photocatalytic reactor under visible irradiation was used for diclofenac (DCF) removal. Different photocatalytic processes including without (Vis/N-TiO2 process) and with hydrogen peroxide (H2O2) (Vis/N-TiO2/H2O2 process) were investigated. Kinetic were identified with different DCF initial concentration in bath condition for both processes. The behaviors of DCF removal by the submerged membrane photocatalytic reactor (SMPR) in combination with reverse osmosis (RO) membrane were carried out in the continuous condition in the long term. The result showed that DCF and TOC concentrations increased in the photocatalytic reactor during operation time. It was a cause of returning DCF molecules and its products to the photocatalytic reactor by the RO membrane rejection. Coupling H2O2 with the photocatalytic process enhanced the DCF and TOC removal by SMPR under the visible irradiation.